Student Intercultural Interaction: Higher School Resources - V I Kazarenkov; A J Siegień-Matyjewicz; T B Kazarenkova (Peoples' Friendship University of Russia (RUDN University), 2013)
The basic aspects of using the higher school resources in forming the knowledge and experience in intercultural interaction (communicative, cognitive, motivational, administrative, emotional) in students are presented in the article; the possibilities of using the integration of classwork and extra-curricular activities for developing the experience in intercultural interaction in the future experts, the need for intercultural dialogue are defined.